Amy is a little bit chicken - Barkley, Callie (Barkley, Callie. Critter Club, 2015)
"Amy has never liked being in the spotlight. When all her friends decide to form a team for the Santa Vista Quiz Bowl, Amy's not so sure. She knows she can answer the quiz questions ... but can she do it in front of hundreds of people? Meanwhile, The Critter Club is caring for some chickens who need a home. As the Quiz Bowl approaches, Amy herself starts feeling just a little bit chicken!"--